STRATEGI MEDIA RELATIONS PUBLIC RELATIONS PT LIPPO CIKARANG, TBK - Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2013)
Public Relations have to cooperate with mass media. In its implementation dealing with journalist, Public Relations should apply strategies and trick to build mutual benefit. The unit of analysis in this research is Public Relations of PT Lippo Cikarang, Tbk. The aim of research is to analyze media relation strategies of Public Relations and aspects of consideration from the strategies at PT Lippo Cikarang, Tbk. Theoretical foundation used is Public Relations strategy known as the Nine Steps of Strategic Public Relations. It consist of four stages that must be applied, Formative Research, Strategy, Tactics, Eva-luative Reseach. The methodology applied is qualitative descriptive, aiming to describe the data systematically, factual, and accurately. Data collection was done through indept interview, observation, and documentation from media relations activities by Public Relations of PT Lippo Cikarang, Tbk. The analy-sis was conducted by using interactive model with Miles and Huberman model consisting of 3 components: data reduction, data display, drawing and verify-ing conclusions. The results showed that there were differentiation in how Pub-lic Relations maintained good relationships with local and national journalists. That's because the editorial policies between local and national media are dif-ferent. In the implementation of its performance, Public Relations of PT Lippo Cikarang Tbk tends to serve national media journalists better than local media journalists. However, the loading of the news about the Lippo Cikarang in the media can exceed the target set, that is more than 80%. That's because the provision of facilities and easy access to information provided by the Public Relations Lippo Cikarang to reporters.